3D stereo pictorial spaces : towards new aesthetics in contemporary painting - Conradi, Ina (Ina Conradi, 2021)
"How much freedom does a space give us, and how does a living space affects its occupation? Stereo photography does not work optically but physiologically, visually: the viewer's perception contributes as much to the image as the camera and the light sensitive plate do. A stereo image is a hybrid of a living experience and a dead picture: you are outside of it, but it is in your head, and you feel it in your body. It takes time for us to see it, time for the experience to construct itself in our perception. Stereo photography cannot be compared to the kind of 3D photography made with disposable cameras; the contours and the space in a stereoscopic viewer are too crisp and uncompromising. Stereo photography isolates and intensifies space, not the people in it. That space is alive, in us, and therefore absolute."